Iowa RBA, June 23, 1997 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1997)
Iowa RBA update for June 23, 1997. Highlights of the update include a Black-headed Gull, a Laughing Gull, a Whimbrel and a Marbled Godwit. Also of note were observations of Mississippi Kites at multiple locations in the central part of the state and Prairie Warblers in Johnson County. Also included are handwritten notes for the next week's update with sightings of a Worm-eating Warbler, a Least Tern, and a Bell's Vireo. Epson - sheet feed/flatbed